Infant and Young Child Feeding Practices upto Two Years of Age and Their Nutritional Status (Bangladesh Medical Journal, 2014)
This cross sectional study was conducted during the period of May 2008 to June 2009, a total of 455 mothers having their children of less than two years of age were interviewed in paediatric OPD of Sir Salimullah Medical College and Mitford Hospital to know the infants and young child feeding practices and their nutritional status. The mothers were mostly from the lower middle and poor socioeconomic condition. About one forth of the mothers had no institutional education. Most of the mothers live in a joint family. Pre-lacteal feeding rate were 60% and most common pre-lacteal food were honey and sugar water. More than 98% mothers gave colostrums to their newborn babies. Over 24% mothers initiated breast feeding within one hour and 18% did so within 30 minutes after birth. Exclusive breastfeeding rate up to 6 completed months of age was found in only 24.4% cases and it was more in educated mothers. Continued breast feeding rate was 34.5% in 19 - 24 months age group of children. About 24% mothers started complementary feeding timely at 6 completed months of age and about 50% mothers started early before 6 months. Most common complementary foods were carbohydrate rich cooked suji, barley or rice powder mixed with either cow's milk or powdered milk. Only 18.5% mother gave khichuri as a complementary food. Bottle feeding was still higher and it was 59.3% cases. In this study, 17.4% children were severely underweight and more than twenty four percent (24.4%) was severely stunted and 2.0% were severely wasted. Malnutrition was common in those children who were nonexclusively breast fed and start complementary feeding either early or late with carbohydrate rich food. DOI: http://dx.doi.org/10.3329/bmj.v41i1.18774 Bangladesh Medical Journal 2012 Vol. 41 No. 1; 14-20